« Ils ont transformé la divinité Yuma en Dieu ! » - Mélanie Vandenhelsken (Ateliers d'Anthropologie)
This article focuses on recent changes in Limbu rituals in Sikkim, and especially the disagreement between a new religious movement called Yumaism—centred on the cult of a young woman considered a reincarnation of the Limbu domestic deity Yuma—and those who think that only shamanism is representative of the Limbu tradition. This disagreement reflects not only divergent conceptions of Limbu religious identity and of the definition and role of ethnic boundaries, but also varying valorisations of Limbu autochthony in Sikkim. Recalling Yuma’s association with Nepalese power and with the Hinduisation of the Limbu in north-eastern Nepal highlighted by Philippe Sagant, this situation reveals a new form of opposition to a renewed cult of Yuma, illustrating a tension between the Limbu’s attachment to their territory, and the connection to wider religious and political networks.